High-level phenol bioproduction by engineered Pichia pastoris in glycerol fed-batch fermentation using an efficient pertraction system - Kumokita, Ryota; Bamba, Takahiro; Yasueda, Hisashi; Tsukida, Ayato; Nakagawa, Keizo; Kitagawa, Tooru; Yoshioka, Tomohisa; Matsuyama, Hideto; Yamamoto, Yasuhito; Maruyama, Satoshi; Hayashi, Takahiro; Kondo, Akihiko; et al. (Bioresource technology, 2024)
[Display omitted] •Metabolic engineering in Pichia pastoris boosts phenol production.•Created a hollow fiber membrane contactor effective for extracting phenol.•Extracted phenol produced by P. pastoris from the fermentation medium.•Demonstrated the potential of pertraction in producing chemicals toxic to microbes. This study aimed to establish a high-level phenol bioproduction system from glycerol through metabolic engineering of the yeast Pichia pastoris (Komagataella phaffii). Introducing tyrosine phenol-lyase to P. pastoris led to a production of 59 mg/L of phenol in flask culture. By employing a strain of P. pastoris that overproduces tyrosine—a precursor to phenol—we achieved a phenol production of 1052 mg/L in glycerol fed-batch fermentation. However, phenol concentrations exceeding 1000 mg/L inhibited P. pastoris growth. A phenol pertraction system utilizing a hollow fiber membrane contactor and tributyrin as the organic solvent was developed to reduce phenol concentration in the culture medium. Integrating this system with glycerol fed-batch fermentation resulted in a 214 % increase in phenol titer (3304 mg/L) compared to glycerol fed-batch fermentation alone. These approaches offer a significant framework for the microbial production of chemicals and materials that are highly toxic to microorganisms.